Safe asset scarcity and re-use in the European repo market - Justus Inhoffen; Iman van Lelyveld (Tinbergen Institute, 2024)
We construct the first measure of collateral re-use at the bank and bond level for the European repo market using a regulatory transaction dataset. We show that banks materially increase the rate of re-use in response to tightened asset scarcity induced by the Eurosystem's asset purchase program. We find that dealers accommodate clients' demand for safe assets rather than liquidity and profit from the repo rate spread. Yet, dealers also re-use collateral to source liquidity which exposes them to collateral runs. Our results contribute to the policy debate on trade-offs between shock absorption and financial stability risks of collateral re-use.
Keywords: E4; E5; G1; G2; 330; collateral reuse; rehypothecation; safe assets; scarcity; repo market